Beach resort development in Indonesia, Malaysia and Thailand. - Tan, Cindy Wen Li. (2008)
This research paper identifies factors that would affect the future developments of beach resort int he next five to ten years in Indonesia. Malaysia and Thailand. The intent is to provide insights as to where the resort industry is heading.